Update on the approach of urinary tract infection in childhood - Ana Cristina Simões e Silva; Eduardo Araújo Oliveira (Elsevier, 2015)
Objective: Urinary tract infection (UTI) is the most common bacterial infection in childhood. UTI may be the sentinel event for underlying renal abnormality. There are still many controversies regarding proper management of UTI. In this review article, the authors discuss recent recommendations for the diagnosis, treatment, prophylaxis, and imaging of UTI in childhood based on evidence, and when this is lacking, based on expert consensus. Sources: Data were obtained after a review of the literature and a search of Pubmed, Embase, Scopus, and Scielo. Summary of the findings: In the first year of life, UTIs are more common in boys (3.7%) than in girls (2%). Signs and symptoms of UTI are very nonspecific, especially in neonates and during childhood; in many cases, fever is the only symptom. Conclusions: Clinical history and physical examination may suggest UTI, but confirmation should be made by urine culture, which must be performed before any antimicrobial agent is given. During childhood, the proper collection of urine is essential to avoid false-positive results. Prompt diagnosis and initiation of treatment is important to prevent long-term renal scarring. Febrile infants with UTIs should undergo renal and bladder ultrasonography. Intravenous antibacterial agents are recommended for neonates and young infants. The authors also advise exclusion of obstructive uropathies as soon as possible and later vesicoureteral reflux, if indicated. Prophylaxis should be considered for cases of high susceptibility to UTI and high risk of renal damage. Resumo: Objetivo: A infecção do trato urinário (ITU) é a infecção bacteriana mais comum na infância. A ITU pode ser o evento sentinela para alteração renal subjacente. Ainda há muitas controvérsias com relação ao tratamento adequado da ITU. Neste artigo de revisão, discutimos as últimas recomendações para diagnóstico, tratamento, profilaxia e imagiologia da ITU na infância, com base em comprovação e, na sua ausência, com base no consenso de especialistas. Fonte de dados: Os dados foram coletados após uma revisão da literatura e pesquisa no Pubmed, Embase, Scopus e Scielo. Resumo dos dados: No primeiro ano de vida, as ITUs são mais comuns em meninos (3,7%) que em meninas (2%). Os sinais e sintomas da ITU são muito inespecíficos, principalmente em neonatos e durante a infância, sendo a febre o único sintoma em muitos casos. Conclusões: O histórico clínico e exame físico podem sugerir ITU, porém a confirmação deve ser feita por urocultura. Antes da administração de qualquer agente antimicrobiano, deve ser feita coleta de urina. Durante a infância, a coleta de urina adequada é essencial para evitar resultados falso-positivos. O diagnóstico e início do tratamento imediatos são importantes na prevenção de cicatriz renal de longo prazo. Neonatos febris com ITUs devem ser submetidos a ultrassonografia renal e da bexiga, Agentes antibacterianos intravenosos são recomendados para neonatos e neonatos jovens. Recomendamos também a exclusão de uropatias obstrutivas o mais rápido possível e posterior refluxo vesico-ureteral, caso indicado. A profilaxia deve ser considerada em casos de elevada susceptibilidade a ITU e risco elevado de danos renais. Keywords: Urinary tract infection, Renal scarring, Ultrasonography, CAKUT, Hydronephrosis, Obstructive uropathy, Palavras-chave: Infecção do trato urinário, Cicatriz renal, Ultrassonografia, CAKUT, Hidronefrose, Uropatia obstrutiva